Risedronate slows or partly reverses cortical and trabecular microarchitectural deterioration in postmenopausal women. - Bala, Y; Chapurlat, R; Cheung, A; Felsenberg, D; LaRoche, M; Morris, E; Reeve, J; Thomas, T; Zanchetta, J; Bock, O; Ghasem-Zadeh, A; Djoumessi, R; et al. (2014)
During early menopause, steady-state bone remodeling is perturbed; the number of basic multicellular units (BMUs) excavating cavities upon the endosteal surface exceeds the number (generated before menopause) concurrently refilling. Later in menopause, steady-state is restored; the many BMUs generated in early menopause refill as similarly large numbers of BMUs concurrently excavate new cavities. We hypothesized that risedronate reduces the number of cavities excavated. However, in younger postmenopausal women, the fewer cavities excavated will still exceed the fewer BMUs now refilling, so net porosity increases, but less than in controls. In older postmenopausal women, the fewer cavities excavated during treatment will be less than the many (generated during early menopause) now refilling, so net porosity decreases and trabecular volumetric bone mineral density (vBMD) increases. We recruited 324 postmenopausal women in two similarly designed double-blind placebo-controlled studies that included 161 younger (Group 1, ≤ 55 years) and 163 older (Group 2, ≥ 55 years) women randomized 2:1 to risedronate 35 mg/week or placebo. High-resolution peripheral computed tomography was used to image the distal radius and tibia. Cortical porosity was quantified using the StrAx1.0 software. Risedronate reduced serum carboxyterminal cross-linking telopeptide of type 1 bone collagen (CTX-1) and serum amino-terminal propeptide of type 1 procollagen (P1NP) by ∼50%. In the younger group, distal radius compact-appearing cortex porosity increased by 4.2% ± 1.6% (p = 0.01) in controls. This was prevented by risedronate. Trabecular vBMD decreased by 3.6% ± 1.4% (p = 0.02) in controls and decreased by 1.6% ± 0.6% (p = 0.005) in the risedronate-treated group. In the older group, changes did not achieve significance apart from a reduction in compact-appearing cortex porosity in the risedronate-treated group (0.9% ± 0.4%, p = 0.047). No between-group differences reached significance. Results were comparable at the distal tibia. Between-group differences were significant for compact-appearing cortex porosity (p = 0.005). Risedronate slows microstructural deterioration in younger and partly reverses it in older postmenopausal women, features likely to contribute to antifracture efficacy.